Trophy -- A New Winter Oat Cultivar for Both Grain and Forage - Ann Blount; Ronald Barnett; Stephen A. Harrison; Cheryl Mackowiak (EDIS)
SS-AGR-282, a 2-page fact sheet by Ann Blount, Ronald Barnett, Stephen A. Harrison, and Cheryl Mackowiak, describes this new winter oat cultivar with considerable potential for grain, forage, conservation tillage, and wildlife purposes in the Southern US. Published by the UF Department of Agronomy, October 2007.